2021
DOI: 10.1002/adma.202008452
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Bio‐Piezoelectric Platforms: From Structures and Synthesis to Applications

Abstract: Piezoelectric materials, with their unique ability for mechanical‐electrical energy conversion, have been widely applied in important fields such as sensing, energy harvesting, wastewater treatment, and catalysis. In recent years, advances in material synthesis and engineering have provided new opportunities for the development of bio‐piezoelectric materials with excellent biocompatibility and piezoelectric performance. Bio‐piezoelectric materials have attracted interdisciplinary research interest due to recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
140
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 234 publications
(237 reference statements)
1
140
0
Order By: Relevance
“… 25,150 Since the direct and converse piezoelectric effects are thermodynamically equivalent, they can be measured to confirm if the measured value indeed truly corresponds to the piezoelectricity of the material. 26 However, due to technical limits, especially in nano-materials, this may not always be possible. The converse effect can be, and has been, quantified at the nano-level using PFM, but it is challenging to quantify the direct effect at such scale as the detection sensitivity of currently existing instruments are not high enough to detect the low output signals from biological materials.…”
Section: Discussion/limitationsmentioning
confidence: 99%
“… 25,150 Since the direct and converse piezoelectric effects are thermodynamically equivalent, they can be measured to confirm if the measured value indeed truly corresponds to the piezoelectricity of the material. 26 However, due to technical limits, especially in nano-materials, this may not always be possible. The converse effect can be, and has been, quantified at the nano-level using PFM, but it is challenging to quantify the direct effect at such scale as the detection sensitivity of currently existing instruments are not high enough to detect the low output signals from biological materials.…”
Section: Discussion/limitationsmentioning
confidence: 99%
“…While there are a number of excellent reviews on soft robots, [ 1–6 ] soft electronic‐skins, [ 7–9 ] flexible wearable devices, [ 10–12 ] rehabilitation and assistive exoskeletons, [ 13–16 ] soft systems in health care, [ 17–20 ] and soft textile Exosuits, [ 21 ] there is currently no review that has a focus on soft actuators and robotic devices specifically developed for soft rehabilitation and assistance. The aim of this review is to investigate the current state‐of‐the‐art technologies in this area to demonstrate the nexus between materials, mechanisms, actuation, and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, insights into future research directions are outlined. systems in health care, [17][18][19][20] and soft textile Exosuits, [21] there is currently no review that has a focus on soft actuators and robotic devices specifically developed for soft rehabilitation and assistance. The aim of this review is to investigate the current state-of-the-art technologies in this area to demonstrate the nexus between materials, mechanisms, actuation, and applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many piezo-catalysts-such as BiFeO 3 , MoS 2 , and g-C 3 N 4 -have been developed to expand their applications in hydrogen generation, sterilization, degradation of organic pollutants, etc. [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the composite piezocatalyst has a different piezoelectric catalytic mechanism to that of single components is also a question worth investigating. For emerging nano-piezo-catalysts, such as MoS 2 , g-C 3 N 4 , studies that have reported them to increase catalytic activities have often focused on tuning the energy level structure in heterogeneous junctions, or adding sacrificial reagent to inhibit the complexation of electrons and holes [15,21]. Studies using cheap and simple methods to achieve spatial separation of electrons and holes in the piezocatalysis process and, thus, to improve the catalytic performance, have not been reported.…”
Section: Introductionmentioning
confidence: 99%